The contribution of activity theory to modeling multi-actor decision-making: A focus on human capital investments - Marocco, Silvia; Talamo, Alessandra (Frontiers in Psychology, 2022)
Making investment decisions is usually considered a challenging task for investors because it is a process based on risky, complex, and consequential choices (Shanmuganathan, 2020). When it comes to Investments in Human Capital (IHC), such as startups fundings, the aspect of decision-making (DM) becomes even more critical since the outcome of the DM process is not completely predictable. Indeed, it has to take into consideration the will, goals, and motivations of each human actor involved: those who invest as well as those who seek investments. We define this specific DM process as Multi-Actor DM (MADM) since not a group is making decisions but different actors, or groups of different actors, who - starting from non-coinciding objectives - need to reach a mutual agreement and converge towards a common goal for the success of the investment. This review aims to give insights on psychological contributions to the study of complex DM processes that deal with IHC to provide scholars and practitioners with a theoretical framework and a tool for describing the complex socio-ecological systems involved in the DM processes. For this purpose, we discuss in the paper how the third generation of Activity Theory (Leont’ev, 1974, 1978; Engeström, 1987, 2001) could be used as an appropriate model to explain the specificities of MADM construct, focusing on the particular case of startup funding. Design Thinking techniques will be proposed as a methodology to create a bridge between different activity systems.